Self-Mapped Learning Pathways: Theoretical Underpinnings and Practical Course Design for Individualized Learning - Matt Crosslin (Arizona State University, 2021)
In the Fall of 2014, several universities came together to offer a unique "dual-layer" open online course. This course was designed with two complete layers from two different course design modalities (instructivism and connectivism). Learners were granted the freedom to create an individualized pathway through the course involving either layer, both layers, or a custom combination of both layers at any given point in the course. Since these options gave learners the ability to map their own pathway as a learning process, this course structure is now referred to as Self-Mapped Learning Pathways. The goal of this design methodology is to allow for true individualization of the learning process for each learner. This article will examine the theoretical underpinnings of Self-Mapped Learning Pathways design methodology. Additionally, several design considerations will be suggested based on practical application as well as research results.